Padronização curricular, padronização da formação docente: desafios da formação pós-BNCC - Hypolito, Álvaro Moreira (2021)
The article aims to analyze the curriculum standardization process imposed by the National Learning Standards -BNCC and its resulting curricular proposals for the initial teacher education courses. Many challenges are posed for post-BNCC teacher education projects, amplified by the pandemic situation that determined an advance in the use of technologies in education, remote education and the expansion of blended education. The sector of production of digital platforms and technologies has deeply entered the educational field in an intense way, taking advantage of the period of the Covid- 19 pandemic to expand in education. The text aims to demonstrate that teacher education policies in this context are local expressions of a global educational reform movement - GERM. The viral dissemination of these policies had a propitious environment in the pandemic context, given the absence of the State for public education, and its stimulation for the expansion of relations between the public and the private sector, which may greatly influence teacher education projects.